String Art and Linear Iterative Systems - Habre, Samer (2013)
String art dates back to the 19th century when it was initially invented to ease the delivery of some mathematical ideas. Since then, the art has evolved and so has its use in mathematics. In this chapter, the authors see how some of the phase portraits for 2 x 2 linear homogeneous iterative systems exhibit some artistic behavior that resembles this form of art. The investigation gives a sufficient condition for the solutions of such systems to form closed cycles. However, in other situations the cycles formed are infinite, producing some fascinating examples of string art.